Upaya Meningkatkan Hasil Belajar Matematika pada Materi Perkalian sebagai Penjumlahan Berulang dengan Penggunaan Media Gambar pada Siswa Kelas III SD Negeri 118272 Aek Kulim Tahun Ajaran 2018/2019 - Saulina Dewi (PGSD UMN Al-Washliyah, 2021)
This study seeks to solve problems in the teaching and learning process in class, with the aim of the research being to increase the activities and results of learning mathematics on the subject of multiplication as repeated addition with the use of image media in grade III students of SD Negeri 118272 Aek Kulim for the 2018/2019 academic year. This study uses Classroom Action Research with a qualitative description approach. The method used to collect data is to use the test method to determine data on student learning outcomes and observation methods for student activities, as well as supporting data in the form of researchers' diaries, for research development using data techniques. The results showed that there was a significant increase in the improvement of student learning outcomes, namely the pre-cycle results: The average score of students was 45.97, and students who scored above the KKM (> 70) were 6 students (19.35% completeness). classically), and those who scored below the KKM (<70) were 25 students (80.65% completeness in classical). Cycle I test results: The average score of students was 68.71, and students who scored above the KKM (> 70) were 16 students (51.61% completeness classically), and those who scored below the KKM (<70) as many as 15 students (48.39% completeness in classical). Cycle II test results: The average score of students is 80.16, and students who score above the KKM (> 70) are 27 students (87.10% completeness classically), and those who score below the KKM (<70) as many as 4 students (12.90%) completeness in classical).